The advent of Tamil drama in Malaysia - Ramachandran, Chitra (Universiti sains malaysia, 1976)
Malaysia is a multiracial, multicultural country. The Chinese and the Indians came here to trade. Some stayed a while, some settled for a longer period of time but eventually they all left for home. With the British intervention and exploitation of Malayan resources, immigrants were brought in to work. As time passed many of the immigrant races made Malaya their home and now form part of Malaysian society.